Optimasi Sintesis Methyl Cellulose (MC) dari Biji Salak (Salacca edulis Reinw) Pondoh Super - Amalia Wahyuningtyas; Agus Setyoko; Sri Anggrahini; Djagal Wiseso Marseno (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
Snake fruit (Salacca zalacca) is one of the typical fruits from Indonesia. Pondoh is one of the snake fruit species largely found in Yogyakarta. The kernels of snake fruit are wastes, but contains a lot of cellulose. Cellulose can be processed into methyl cellulose And be used as food additive. This study aimed to understand the optimized the optimizing synthesis of methyl cellulose through the concentration of NaOH, dimethyl sulfate and reaction temperature. The study was conducted by extracting cellulose using 4 % NaOH concentrations. Dehemicellulose and bleaching were done to dilute hemicellulose and lignin. The optimization of methyl cellulose was done using Response Surface Methodology with various concentrations of NaOH (10, 15, 20, 25, 30%), dimethyl sulfate (2, 3, 4, 5, 6 ml), and temperature (45, 50, 55, 60, 65Â°C). NaOH could change cellulose crystalline region and formed Na-cellulose. Dimethyl sulfate can be acted as substitution agent, while temperature controlling plays role to obtain appropriate conditions for reaction. The results showed that the use of NaOH concentration, dimethyl sulfate and temperature affected the degree of substitution, OHC and lightness. The addition of NaOH and dimethyl sulfate in producing methyl cellulose had more effect on the increasing of degree of substitution than temperature treatment. The optimum condition of methyl cellulose were 0.91% NaOH; 3.52 ml of dimethyl sulfate, at 46.51Â°C temperature.